No moderating effect of 5-HTTLPR on associations between antenatal anxiety and infant behavior - Braithwaite, E; Ramchandani, P; O'Connor, T; Van Ijzendoorn, M; Bakermans-Kranenburg, M; Glover, V; Netsi, E; Evans, J; Meaney, M; Murphy, SE (2013)
Objective: Maternal antenatal anxiety is associated with an increased risk of behavioral disturbances in offspring. Recent work has suggested that the effect of maternal antenatal anxiety on infant temperament at 6 months is moderated by the serotonin transporter polymorphism 5-HTTLPR, with carriers of the short allele more susceptible to the adverse behavioral outcomes of maternal antenatal anxiety. These findings, however, are yet to be replicated and extended beyond infancy. The aim of the current study was to assess this same potential moderator (5-HTTLPR) in a large population-based cohort study, and to determine whether or not the effects persist into childhood and early adolescence. Method: Data from the Avon Longitudinal Study of Children and Parents (ALSPAC) cohort (N = 3,946) were used to assess whether the 5-HTTLPR genotype moderated the association between self-reported maternal antenatal anxiety (Crown Crisp Index) in pregnancy, and child temperament at 6 months (Infant Temperament Questionnaire), and also later behavioral and emotional problems on the Strengths and Difficulties Questionnaire from age 4 to 13 years. Results: We found no evidence to suggest that the 5-HTTLPR polymorphism moderated the effects of maternal antenatal anxiety on infant temperament at 6 months or infant behavioral and emotional problems from childhood through to adolescence. Conclusion: Our results, based on a large prospective community sample that assessed children from infancy to early adolescence, provide a thorough test of, but no evidence for, a genetic moderation of the effects of maternal antenatal anxiety by 5-HTTLPR. © 2013 American Academy of Child and Adolescent Psychiatry.